رعایا کےلیے اصول نظم و ضبط اوراسلامی تعلیمات: The Ways of Disposing Public In The Light of Islamic Teachings - Sara Noor; Dr.Noor Hayat Khan (MEI, 2023)
Islam is an organized religion which provides complete code of life through a proper social and moral system. We see prophet Muhammad (SAW) providing practical guide guidelines for a stable and comprehensive society. The madni life of Muhammad (SAW) is a best and practical example of Islamic executive fairness, equality and social security. The paper deal with the concept of topic, significance, objectives and statements of disposing role of the prophet Muhammad (SAW) in establishing a balanced society. These teachings and concepts show that Islam is not only the religion of theories but has governance in the administration pattern and training to manage a stable and sensitive system of state which highlights the importance of highly managed system of Islam. Human being is a social animal prepare to live with society. Everyone in the society has some rules to play his responsibility to achieve the common goals of society. In order to organize these activities there should be a stable and affective managed system. The people of the whole world has observed that the Muslims influenced with the help of their managerial abilities while spreading peace, high-level education, most recent resilient army, practicable laws etc